Effectiveness of digitization of receipts to financial records security in online platforms - Diron, Sittie Ainah H. Elamparo, France Aldrek A. Licudo, Chlo'e Anne D. Mariano, Ma. Angeline M. Ordiz, Marion S. Panganiban, Michelle Anne G. Sangalang, Princess Shaira C. 4 0 16; 5
ABSTRACT: Receipts are a requirement for businesses to keep track of their financial records such as their income and expenses. Due to the pressure of digital transformation, businesses from different sectors have been subjected to turn to ecommerce. The slow transition into a paperless society has proven to be more effective in cutting costs and providing business with a much more efficient and convenient way of recording, storing, and reconciling their transactions. This research paper evaluates the digitization of receipts to completeness of financial data, safety of customer information, and protection from financial theft particularly in the Micro and Small enterprises in the City of Manila. The study aims to encourage small business owners to utilize digital receipts as it is more efficient in accounting for their day-to-day transactions. The study also presents the problems encountered by businesses in transacting online. The researchers utilized the quantitative research method with a descriptive research design for the study. Purposive sampling is used in gathering respondents engaging in online platforms in Manila City. A total of 162 online business owners were successfully gathered. Survey questionnaire is the main instrument used in accumulating data required by the study. In the four-part questionnaire, the results showed that problems presented in table 3 of the paper have a low chance of occurring as observed by half of the population size. With this, digital receipts are said to be sustainable for the business. Table 4 states the influence of digital receipts on the completeness of financial data. The results revealed that the former has a high positive influence towards the latter, and that digital receipts can ensure that businesses have accurate financial records. Table 5 depicts the influence of 5 digital receipts on the safety of customer information. Contrary to the past results, respondents observed that digital receipts have a high negative influence on keeping customer information. Lastly, Table 6 talks about the influence of digital receipts towards the protection from financial theft. Similarly, resulting in a high negative influence.
Research Paper: (Bachelor of Science in Accountancy) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2